Influence of Public Aid Coming from Self-Government Sector on Economic Development (Concept of The Research) - Magdalena KOGUT-JAWORSKA (Communications of International Proceedings, 2020)
Expectation concerning the public sector role are steadily growing. They concentrate not only on the traditional regulatory and stabilizing role of the state, but on the active participation as well. The expectations are aimed at creating proper conditions for economic development. Public aid is one of the tools applied in order to meet the goals set for public policies. Effectiveness of public aid application is a crucial issue, having in mind a high level of pressure on more economical expenditure of the means available. Secondly, public aid is always targeted at the chosen subjects, which has influence on the competition and on the market. However, it may also have negative impact on the market. Research on public aid effectiveness includes some elements of balancing the negative and positive elements of the aid application.
Keywords: Public Aid; Public Finance; Self-Government Finance Economic Development; Regional Policy